KOMUNIKASI HUMANIS - Ujang Mahadi (Institut Agama Islam Negeri Bengkulu, 2017)
Humans are perfect creatures that are unique, active, creative, dynamic, have ideology, breed, have lust, will and can act. In addition, human beings are creatures who think, have personality, have awareness and responsibility. Humans are social beings who can not live alone, in fulfilling the needs of human life requires and interact with other humans. Communication between people always takes place in a value-packed atmosphere, such as ideology, tradition, political orientation, world view (word view) and even religion. Thus the communication process is always influenced by the factors of cultural situation adopted by society, the patterns of social relationships that grow and develop in a society, and the physical environment in which the communication process takes place. The essence of humanist communication is humanizing human beings, namely the effort to give attention, appreciation, respect, love values, affection, and empathy in communicating.